Unfolding the physics of URu2Si2 through silicon to phosphorus substitution - A. Gallagher; K.-W. Chen; C. M. Moir; S. K. Cary; F. Kametani; N. Kikugawa; D. Graf; T. E. Albrecht-Schmitt; S. C. Riggs; A. Shekhter; R. E. Baumbach (Nature Communications, 2016)
The heavy fermion compound URu2Si2displays a hidden order phase and superconductivity at low temperatures. Here, the authors perform substitution studies—partially replacing silicon with phosphorus—and study the effects on hidden order and superconductivity.